2013
DOI: 10.1142/s0219498813500540
|View full text |Cite
|
Sign up to set email alerts
|

ON TENSOR PRODUCT DECOMPOSITION OF $\widehat{\mathfrak{sl}}(n)$ MODULES

Abstract: Communicated by E. ZelmanovWe decompose the b sl(n)-module V (Λ 0 ) ⊗ V (Λ 0 ) and give generating function identities for the outer multiplicities. In the process we discover an infinite family of partition identities, which are seemingly new even in the n = 3 case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As pointed out in [24], combining (2.6.6) with the results from [8] leads to new proofs of certain identities listed in [28]. [3,6] is sufficient to actually compute the limit in Proposition 2.6.1.…”
Section: 3mentioning
confidence: 89%
See 3 more Smart Citations
“…As pointed out in [24], combining (2.6.6) with the results from [8] leads to new proofs of certain identities listed in [28]. [3,6] is sufficient to actually compute the limit in Proposition 2.6.1.…”
Section: 3mentioning
confidence: 89%
“…However, it is well-known that more direct descriptions lead to deep connections with combinatorics, number theory, and mathematical physics. For instance, in the case of affine Lie algebras this leads to proofs of Rogers-Ramanujan-type identities as well as partition identities (see [8,20,24,25] and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [17], we considered the case i = 0 for n = 2, 3 and showed that we obtain certain identities in the Slater list [18] and some new identities for i = 0 and n = 3. In this paper we consider the case i = 1 for n = 2, 3, 4 and obtain some seemingly new identities.…”
Section: Examples and Identitiesmentioning
confidence: 99%